DIALEKTIKA FEMINIS INDONESIA TERHADAP UNDANG-UNDANG POLIGAMI - Ivan Majeda; Musolli Musolli (LPPM UNHASY, 2023)
This study aims to trace Husein Muhammad’s reason thinking, Indonesian feminist Kyai in the case of licensing polygamy according to the Compilation of Islamic Law. Husein Muhammad is one of the pesantren kiai who is intense in gender issues. The idea offered by Husein Muhammad is reinterpretation of gender-biased legal issues in the hope that it can be used as a guide and guide in dealing with particular problems at the present time. This study seeks to unravel the views of KH. Husein Muhammad on gender justice in polygamy permits. This research is a qualitative research literature (library research). The technique used in analyzing the data in this study, using descriptive-analytical method, to describe in general the thoughts of Husein Muhammad. The data for this research are books written by Husein Muhammad and interviews with him. This study concludes that Husein Muhammad's method of thinking in rejecting the rules for licensing polygamy according to the rules of the Compilation of Islamic Law is based on the concepts of selection (intiqo-iy) and exploration (ijtihad). These two concepts are oriented towards the concept of protecting and providing a sense of justice for women which can be integrated into Indonesian positive law. Keywords: Feminist kyai, Critical reasoning, Polygamy laws Daftar Pustaka Al Amin, Habibi.